227 THE PROGNOSTIC VALUE OF RIGHT ATRIAL STRAIN IN PATIENTS WITH SECONDARY TRICUSPID REGURGITATION. (15th December 2022) - Tomaselli, Michele; Paolo Badano, Luigi; Paolo Perelli, Francesco; Radu, Noela; Oliverio, Giorgio; Francesca, Heilbron; Stucchi, Davide; Pece, Cinzia; Camponetti, Virginia; Cascella, Andrea; Caravita, Sergio; Baratto, Claudia; et al.
Abstract: Background: in secondary tricuspid regurgitation (STR), the remodeling of the right ventricle (RV) and the right atrium (RA) is associated with different outcomes. However, the potential prognostic role of right RA function in this setting, assessed by 2D-speckle tracking echocardiography (2D-STE), remains to be tested. Accordingly, the aim of our study is to assess the prognostic value of RA 2D-STE in patients with significant (i.e. moderate or severe) STR. Methods: we retrospectively studied 227 (mean age 74±14, 40% men, 59% sinus rhythm) consecutive patients with significant STR, acquired between May 2012 and June 2021. RA 2D-STE was obtained from a dedicated, non-foreshortened RV-focused apical 4-ch view, using a dedicated software package (AFI LA, EchoPAC 204, GE Vingmed, Horten, Norway). Among the three longitudinal strain components provided by the software package (reservoir, conduit and, contraction), we focused on RA longitudinal strain during reservoir (RASR). Patients were divided into two groups according to the median value of RARS (12%). A combined endpoint of heart failure hospitalization and all-cause mortality was defined. Results: after a median follow-up period of 14 months (IQR, 1-27), 93 patients (41%) reached the combined endpoint. The predictive power of RARS<12% (AUC 0.64 [IC 95% 0.56-0.71]), was significantly higher than RA maximum volume (AUC 0.38 [IC 95% 0.31-0.47]). Patients with RARS ≤ 12% were more symptomatic (according to NYHA class), had larger RA volumes (119 vs 89 mL, p<0.001) and, a reduced right ventricular systolic function (TAPSE: 14.7 vs 18.9 mm; FAC 37.7 vs 42.4%; RV free-wall strain: 17.5 vs 20.8%; all p<0.001). In addition, patients with RARS<12% had more severe TR (corrected EROA: 0.85 vs 0.41 cm 2 ; p<0.05). Prevalence of atrial fibrillation (58 vs 61%), left ventricular ejection fraction, and right ventricular size were similar between the groups. Patients with RARS ≤12% had a significant risk for death (log rank, p<0.001), even after correcting for confounding variables. Moreover, RA strain was independently associated with the combined endopoint in multivariate analysis (p < 0.001) Figure 1. Kaplan-Meier curve for time to cumulative events, according to RARS (>12% red line, ≤12% black line). Conclusions: in patients with significant STR, RARS is an independent predictor of the combined endpoint of heart failure hospitalization and all-cause mortality and provides incremental prognostic value over RA volume.